2015
DOI: 10.1039/c5ra11459d
|View full text |Cite
|
Sign up to set email alerts
|

Compressed sodalite-like MgH6 as a potential high-temperature superconductor

Abstract: Recently, an experimental work reported a very high Tc of ~190K in hydrogen sulphide (H2S) at 200 GPa. The search of new superconductors with high superconducting critical temperatures in hydrogen-dominated materials has attracted significant attention. Here we predict a candidate phase of MgH6 with a sodalite-like framework in conjunction with firstprinciples electronic structure calculations. The calculated formation enthalpy suggests that it is thermodynamically stable above 263 GPa relative to MgH2 and sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(164 citation statements)
references
References 36 publications
8
154
0
2
Order By: Relevance
“…Calculations have predicted that hydrogenic sodalite-like lattices will also be found in MgH 6 around 260 GPa [34] and YH 6 at 120 GPa [61].…”
Section: How To Metallize With An Electropositive Elementmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations have predicted that hydrogenic sodalite-like lattices will also be found in MgH 6 around 260 GPa [34] and YH 6 at 120 GPa [61].…”
Section: How To Metallize With An Electropositive Elementmentioning
confidence: 99%
“…Therefore, building on Ashcroft's proposals, density functional theory (DFT) calculations were carried out to predict the structures of hydrides with stoichiometries that are not stable at atmospheric conditions, in the hopes of uncovering hitherto unknown superconductors [19]. Since then, numerous theoretical studies have been performed that investigate the phase diagrams of hydrogen doped with the electropositive alkali metals or alkaline earth metals [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], as well as the electronegative element iodine [35,36] under pressure. Experimental work on the hydrides of lithium and sodium confirmed that species with unique stoichiometries such as NaH 3 and NaH 7 can be synthesized in diamond anvil cells, but the phases that have been reported to date do not exhibit superconductivity [21,37].…”
Section: Introductionmentioning
confidence: 99%
“…This group made several other interesting predictions, which are waiting their future confirmations (Peng et al,2017;see the review by Zhang et al,2017). They predicted the high T c superconducting state for calcium hydride (T c ≈240K; Wang et al,2014) and for YH 6 (T c ≈264K; Li et al,2015).Note that the compound MgH 6 ,similar to CaH 6 was also studied (Feng et al,2015) and the values of Tc ≈ 260K at P ! > 300GPa were predicted.…”
Section: Other Hydridesmentioning
confidence: 99%
“…Wherein the measured critical temperature (T C ) of 203 K in hydrogen sulfide is among the highest over allknown superconductors [5]. The theoretical studies have revealed a significantly more superconducting hydrogenrich materials such as PtH [7,8], H 2 S [9], GaH 3 [10,11], ScH 3 [12,13], SnH 4 [14], GeH 4 [15,16], NbH 4 [17,18], CaH 6 [19], MgH 6 [20] of which the highest critical temperature equal to 263−271 K was estimated for MgH 6 compound at a pressure range from 300 to 400 GPa [20]. As it turns out pressure (p) can have a very large impact on the critical temperature and thermodynamics of superconducting state.…”
Section: Introductionmentioning
confidence: 99%